Phase II study of tirapazamine plus cisplatin in patients with advanced or recurrent cervical cancer. Issue 3 (1st April 2006) - Maluf, F. C.; Leiser, A. L.; Aghajanian, C.; Sabbatini, P.; Pezzulli, S.; Chi, D. S.; Wolf, J. K.; Levenback, C.; Loh, E.; Spriggs, D. R.
Abstract : The aim of this study was to evaluate the activity and toxicity of a tirapazamine (TPZ)/cisplatin drug combination in patients with stage IV or recurrent cervical cancer. The chemotherapy was administered for a maximum of eight cycles every 21 days. TPZ was administered intravenously at 330 mg/m 2 over a 2-h infusion, followed 1 h later by cisplatin intravenously at 75 mg/m 2 over 1 h on day 1. All patients received antiemetics including dexamethasone, ondansetron, and lorazepam. Subsequent doses were unchanged, reduced, or omitted according to observed toxicity and protocol guidelines. Response evaluation was performed every two cycles. Thirty-six patients with stage IV or recurrent cervical cancer were treated. Ninety-four percent of patients had prior radiotherapy. Two patients had prior chemotherapy. There were two complete responses and eight partial responses (27.8%). An additional 11 patients (30.6%) had stable disease as their best response. Response rate was greater in tumors outside of the previously radiated field (44.4% vs 11.1%). The median time to progression was 32.7 weeks. The most frequent grade 3 or 4 adverse events were nausea, vomiting, and fatigue, which occurred in 30.6%, 25%, and 22% of subjects, respectively. Anemia was the most frequent grade 3 or 4 hematologic toxicity at 8.3%. We conclude that the combination of cisplatin and TPZ was reasonably well tolerated in patients with recurrent or advanced cervical cancer. Further evaluation of this drug combination may be warranted.